Reaksi pasar saham atas peristiwa disahkannya Omnibus Law RUU Cipta Kerja - Sutrisno, Yeni Hairida; Swandari, Fifi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This research aims to analyze stock market reaction on the legalization of Omnibus Law the Job Creation Act on October 5, 2020. The market reaction is measured using abnormal return, average abnormal return and trading volume activity which happens in manufacturing company consumer goods sector food and beverage sub sector listed on the Indonesia Stock Exchange. The research sample is determined by using non probability sampling method with purposive sampling technique. Hypothesis testing used one sample t-test and wilcoxon signed rank test in which the observation period is 15 days using SPSS tools. The results of the hypothesis testing show that there is a significant abnormal return on the 3rd day dan 7th day after the Job Creation Act legalization. There is no significant difference in the average abnormal return between the period before and after the Job Creation Act legalization. There is no significant difference in the trading volume activity between the period before and after the Job Creation Act legalization.